Promoting Sustainable Development While Building Upon Components of Reading Literacy (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
The paper sheds light on the evaluation of books for pre-school children and the theory of reading children’s literature while bearing in mind the various components of reading literacy. Like reading literacy, education on sustainability is also a life-long process, and for understanding the concept of sustainability and the role of the individual in its implementation, which begins to form in the pre-school period, we chose the work by Adèle Tariel and Julie de Terssac 1000 Cows (French original: 1000 vaches), which indicates that illustrations affect the comprehension of the story and (at least partially) change or present more clearly the key morphological characteristics of the text. We conducted a case study in which we included part-time students from the third year of Early Childhood Education Studies (n = 13). An analysis of the content of responses was carried out. These demonstrate a broad semantic field of understanding literary-artistic reading and represent an example of interdisciplinary integration that can significantly contribute to the development of components of reading literacy as well as a sustainable future.